The impact of the franchisor-franchisee relationship on franchisee performance - Sun, Xiaoxi (2021)
Franchising, as an organisational form, has received much attention from both researchers and practitioners. Many studies have examined various aspects of franchising from either the franchisor’s or the franchisee’s perspective. However, little research has linked the perspectives of both franchisor and franchisee. Given the importance of the relationship between franchisor and franchisee, this thesis presents an integrative view that analyses franchise performance in China at the individual franchisee level. For simplicity, this has been shortened to “franchisee performance” and includes both franchisee financial performance and franchisee satisfaction. Agency theory, the resource-based perspective and a relational view were combined to understand the factors influencing franchise performance. In the context of franchising as a mutual relationship, the key factors analysed were the franchisor’s control mechanisms, the franchisee’s pooled resources with those of the franchisor, and the relationship between franchisor and franchisee. Ten main hypotheses and twelve sub-hypotheses were developed and tested. The analysis was based primarily on a survey of three franchisors and their franchisees in nine provinces. 351 usable questionnaires were collected from franchisees, with a response rate of 43%. Confirmatory factor analysis was used to test the measurement model and the structural model. Hypotheses were tested using Smart PLS. Twenty semi-structured interviews were conducted to understand the franchisor-franchisee relationship in more depth. ii The results provided valuable insights into franchisee performance. The franchisor’s level of control over a franchise had a positive influence on franchisees’ satisfaction. Franchisees’ resources complementing those of the franchisor had a significant positive effect on both franchisee satisfaction and financial performance. Relational factors, in particular trust and absence of opportunism, had a significant mediation effect on franchisee performance. An unexpected statistically significant finding was that information sharing reduced franchise performance. This thesis makes a theoretical contribution as it shows the limitations of agency theory and its focus on legal contracts in understanding the franchisor franchisee relationship. A franchise relationship is a two-way relationship, especially in China, not merely a one-way principal-agent relationship as proposed in agency theory. The thesis also shows the value of integrating franchisor and franchisee perspectives in analysing franchising, for example, the importance of pooled resources between franchisor and franchisee in the light of the resource-based perspective and relational view in China. The thesis’ practical implications include the need for franchisors to consider the franchisee relationship as multi-dimensional rather than just a formal contractual relationship, especially in China where social relationships are important both before and after a contract is signed. Directions for future research include using this integrated relational view of franchising beyond China; analysis of control mechanisms in franchising; and the role of knowledge sharing. Developing more reliable measurements of franchise performance in emerging economies such as China would also be valuable.